2020
DOI: 10.1038/s41598-020-74407-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcomes in patients with mitral regurgitation undergoing percutaneous valve repair

Abstract: Percutaneous mitral valve repair has been increasingly performed worldwide after approval. We sought to investigate predictors of clinical outcome in patients with mitral regurgitation undergoing percutaneous valve repair. The MITRA-UMG study, a single-centre registry, retrospectively collected consecutive patients with symptomatic moderate-to-severe or severe MR undergoing MitraClip therapy. The primary endpoint was the composite of cardiovascular death or rehospitalization for heart failure. Between March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Moreover, Polimeni et al have recently concluded that LVEDVi and NYHA class are predictors of rehospitalization for heart failure or cardiovascular death in patients having MitraClip system. Thus, the continued effective MR reduction with improved NYHA class for 1 year in our study could increase the survival and reduce the rehospitalization rate in MR patients [23].…”
Section: Clinical Outcome and Follow-upmentioning
confidence: 65%
“…Moreover, Polimeni et al have recently concluded that LVEDVi and NYHA class are predictors of rehospitalization for heart failure or cardiovascular death in patients having MitraClip system. Thus, the continued effective MR reduction with improved NYHA class for 1 year in our study could increase the survival and reduce the rehospitalization rate in MR patients [23].…”
Section: Clinical Outcome and Follow-upmentioning
confidence: 65%
“…The benefits resulting from TEER in terms of global improvement of cardiac function assessed by basal and advanced echocardiographic imaging modalities have been extensively described [ 26 , 27 ]. More in detail, it has been demonstrated that LA strain measurements offer the highest diagnostic accuracy, sensitivity, and specificity in predicting elevated LV filling pressures while providing a close figure of pulmonary capillary wedge pressure in HF [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Buzzatti et al reported higher prevalence of coronary artery disease and CRT in FMR patients, whereas other comorbidities were equally distributed among patients with SMR and FMR [ 12 ]. Polimeni et al revealed higher prevalence of diabetes, prior revascularization and myocardial infarction in FMR patients, while there was no significant difference in other concomitant diseases [ 13 ]. Meta-analyses that included 2351 patients showed that diabetes, previous myocardial infarction, renal insufficiency, coronary artery bypass grafting, percutaneous coronary intervention and cardiac resynchronization therapy were more prevalent among FMR patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%